2021
DOI: 10.1021/acsami.0c21696
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Droplet Arrays in Thermosetting Oil for Dynamic Proteolytic Assays of Single Cells

Abstract: Matrix metalloproteinases (MMPs) play an important role in tumor progression. The study of dynamic MMPs activity at the single-cell level can dissect tumor heterogeneity in the time domain and facilitate finding out more efficient clinical solutions for tumor treatment. Due to the fluidity of the carrier oil, the existing droplet-based methods for single-cell MMP analysis rarely have the capability to track proteolytic assays in droplets continuously. Therefore, we describe a thermosetting oil for realtime mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…For instance, the comparison of the glycerol produced by an adipocyte cell line and adipose-tissue derived cells has revealed a unique secretory oscillatory pattern from the tissue explant . In the same vein, the measurement of the kinetics of ECM proteolysis using FRET-based sensors in droplet revealed intrapopulation heterogeneity in terms of dynamics and level of MMP production within large populations of cancer cells. , …”
Section: Characterizing Cell Behaviormentioning
confidence: 99%
“…For instance, the comparison of the glycerol produced by an adipocyte cell line and adipose-tissue derived cells has revealed a unique secretory oscillatory pattern from the tissue explant . In the same vein, the measurement of the kinetics of ECM proteolysis using FRET-based sensors in droplet revealed intrapopulation heterogeneity in terms of dynamics and level of MMP production within large populations of cancer cells. , …”
Section: Characterizing Cell Behaviormentioning
confidence: 99%
“…7B). 135 This method can enable the realtime monitoring of single-cell proteolytic activity without com-…”
Section: Critical Review Analystmentioning
confidence: 99%
“…Secreted products such as matrix metalloproteinases (MMPs) represent promising drug targets and biomarker candidates and provide valuable information for evaluating cancer metastasis and, based on an analysis of their activity, allow for the screening of new drugs to regulate inflammatory responses and tumorigenesis. 133–135 Yu et al reported a microfluidic approach for the detection of MMP9 (a gelatinase subgroup of MMPs) enzyme activity in individual tumor cell droplets using a flow-focusing capillary microfluidic device (Fig. 7A).…”
Section: Biomedical Applications Of Single-cell Droplets and Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the diaphragm, that is, the solidified thermosetting oil with nanochannels between adjacent droplets, is used as a dialysis membrane to allow water to transfer freely between the droplets with different osmotic pressures and deform or even rupture. 41 Therefore, we determine the stability of the thermally solidified droplets by observing the migration of fluo- rescence in the droplets under a fluorescence microscope. After droplet generation, the sealed microfluidic chip was incubated at 37 °C and photographed at 2, 4, 6 and 18 hours to determine the percentage of intact droplets.…”
Section: Properties and Stability Of The Thermosetting Oil-based Drop...mentioning
confidence: 99%